DnaK Protein Alleviates Toxicity Induced by Citrate-Coated Gold Nanoparticles in Escherichia coli - Makumire, Stanley; Revaprasadu, Neerish; Shonhai, Addmore (PLOS ONE, 2015)
A number of previously reported studies suggest that synthetic gold nanoparticles (AuNPs) are capable of stabilising proteins against heat stress in vitro. However, it remains to be understood if AuNPs confer stability to proteins against cellular stress in vivo. Heat shock proteins (Hsps) are conserved molecules whose main role is to facilitate folding of other proteins (chaperone function). Hsp70 (called DnaK in prokaryotes) is one of the most prominent molecular chaperones. Since gold nanoparticles exhibit chaperone-like function in vitro, we investigated the effect of citrate-coated gold nanoparticles on the growth of E. coli BB1553 cells that possess a deleted dnaK gene. We further investigated the effects of the AuNPs on the solubility of the E. coli BB1553 proteome. E. coli BB1553 cells exposed to AuNPs exhibited cellular defects such as filamentation and plasma membranes pulled off the cell wall. The toxic effects of the AuNPs were alleviated by transforming the E. coli BB1553 cells with a construct expressing DnaK. We also noted that cells in which DnaK was restored exhibited distinct zones to which the nanoparticles were restricted. Our study suggests a role for DnaK in alleviating nanoparticle induced stress in E. coli.